Isolation and Detection of Extended Spectrum β‐Lactamase (ESBL)‐Producing Enterobacteriaceae from Meat using Chromogenic Agars and Isothermal Loop‐Mediated Amplification (LAMP) Assays. Issue 12 (December 2013) - Anjum, M.F.; Lemma, F.; Cork, D.J.; Meunier, D.; Murphy, N.; North, S.E.; Woodford, N.; Haines, J.; Randall, L.P.
Abstract: The aim of this work was to develop a molecular method using loop‐mediated isothermal amplification (LAMP) for detection of extended spectrum β‐lactamase (ESBL)‐producing Enterobacteriaceae from meat, and to compare it with different isolation agars and microarrays. LAMP assays were developed for CTX‐M groups 1, 2, and 9 and OXA‐10‐like genes. Chicken, lamb, beef, pork, and turkey samples were spiked with 10, 100, and 1, 000 cfu/gram using 8 strains of ESBL‐producing Enterobacteriaceae (CTX‐M sequence types 1, 2, 3, 14, 15, OXA‐11, SHV‐2, TEM‐52) +/– a mix of competitor organisms. Samples were enriched overnight in buffered peptone water (BPW) +/– antibacterials before plating to CHROMagar CTX, OXOID ESBL Brilliance agar, and MacConkey agar with 1 mg/L cefotaxime. Selected BPW broths were also tested using LAMP assays, microarrays and using cefpodoxime discs on agar. For isolation/detection of ESBL producers from beef, pork, lamb, and turkey spiked with 10 or 100 cfu/gram ESBL (natural flora only), all agars and the LAMP assays showed 100% sensitivity and specificity for ESBL spike strains. For chicken samples, both LAMP and chromogenic agars showed improved sensitivity and specificity for isolation of ESBLs compared with MacConkey agar, particularly with competitor bacteria added. In comparison, the cefpodoxime disc method and microarray showed reduced sensitivity.